Drought adaptive prediction in potato (Solanum tuberosum) using in vitro and in vivo approaches - JANE KATHRYNE JOLANDA LAISINA; AWANG MAHARIJAYA; SOBIR SOBIR; AGUS PURWITO (Society for Indonesian Biodiversity, 2021)
Abstract. Laisina JKJ, Maharijaya A, Sobir, Purwito A. 2021. Drought adaptive prediction in potato (Solanum tuberosum) using in vitro and in vivo approaches. Biodiversitas 22: 537-545. Prediction of drought adaptive potatoes requires selection indicators. This study aimed to determine in vitro selection indicators for obtaining drought adaptive potato genotypes in vitro and in vivo. The in vitro study was performed using single-node explants from seven genotypes cultured for six weeks on MS medium added with 0.2 M sorbitol to achieve the research aims. The cultures were partially observed and followed by watering the in vitro tubing medium. For the in vivo study, drought stress was applied for 21 days when the plants reached 25 days after planting (DAP) and for 14 days when the plants reached 50 DAP, then plants were irrigated again until harvesting. The results showed that plant height and root length can be used as selection indicators because they had a relative decrease below 50%, a close relationship and had the same variance with the in vitro number of tubers, in vitro tuber fresh weight and in vivo tuber fresh weight in drought stress at 25 DAP. These characters were determinant characters for the clustering pattern in the heat map cluster analysis. Based on these characters, SSI analysis was also performed and it was found that the PKHT4 was more adaptive than the PKHT6 in vitro, but the two genotypes were classified in the medium adaptive in vivo. In conclusion, plant height and root length were determined as the in vitro selection indicators in predicting drought adaptive genotypes in vivo at the plant age of 25 DAP.